Determinants of Oil Palm Farmers’ Welfare in Aceh, Indonesia - Haykal, Muhammad; Yunus, Saifuddin (The journal of contemporary issues in business and government, 2021)
This study examines the determinants of the welfare of oil palm farmers in Aceh, Indonesia. The main focus of this study is on the current price of oil palm, whether it affects the level of welfare of oil palm farmers or not and what efforts the government has made to improve the farmers’ welfare. This research applies quantitative descriptive approach. The number of samples was 70 Aceh farmers in 24 districts in east Aceh. The selected famers who have been designated as farm owners and workers. The sampling technique used is judgment sampling. The research data collected by using a closed questionnaire. The results of the study found that when the price of palm oil is unstable, farmers must be able to process by-products in an effort to maintain the welfare of their families. In testing the two models, the same results were obtained, this cost could not be controlled by the farmers, especially the maintenance costs using industrial processed products such as fertilizers and pesticides. Therefore, the government must further intensify the economic empowerment programs for oil palm farmers. More programs for people are still required. During the Pandemic Covid-19, farmers only relies on the sale of fresh fruit bunches (FFB) at fluctuating prices which decreases farmers' income thus making them unable to improve their welfare.